A Factors Affecting the Incidence of Diarrhea in Toddlers in the Working Area of the Birobuli Health Center, Palu City - Tantri Utami; Rabiah Rabiah; Maryam Maryam; Yulta Kadang (An Idea Health Journal, 2022)
This research is quantitative and used descriptive research design, which aimed to see the influencing factors of Diarrhea incidence at working are of Birobuli Public Health center of Palu city. The samples of the research were 30 respondents. The data analyzes used Univariate, the variable measured by using questionnaire.The finding of the research shows the influencing factors of Diarrhea incidence. Fisrtly, it can be seen from breast milk (Air Susu Ibu) in good category with 53,3% percentage and breast milk in less good category with 46,7% percentage. Secondly, healthy life style in good category with 80,0% percentage and healthy life style in less good category with 20,0% percentage. Lastly, mother’s knowledge in good category with 53,33% percentage and mother’s knowledge in less category with 46,66% percentage.The collected data analyzed by using SPSS program. Univariate analysis is used decide the variable frequency distribution, which results distribution and percentage of each variable.